Changes in subcutaneous white adipose tissue cellular composition and molecular programs underlie glucose intolerance in persons with HIV - Bailin, Samuel S.; Kropski, Jonathan A.; Gangula, Rama D.; Hannah, LaToya; Simmons, Joshua D.; Mashayekhi, Mona; Ye, Fei; Fan, Run; Mallal, Simon; Warren, Christian M.; Kalams, Spyros A.; Gabriel, Curtis L.; et al. (Frontiers in Immunology, 2023)
Subcutaneous adipose tissue (SAT) is a critical regulator of systemic metabolic homeostasis. Persons with HIV (PWH) have an increased risk of metabolic diseases and significant alterations in the SAT immune environment compared with the general population. We generated a comprehensive singlecell multi-omic SAT atlas to characterize cellular compositional and transcriptional changes in 59 PWH across a spectrum of metabolic health. Glucose intolerance was associated with increased lipidassociated macrophages, CD4 + and CD8 + T effector memory cells, and decreased perivascular macrophages. We observed a coordinated intercellular regulatory program which enriched for genes related to inflammation and lipid-processing across multiple cell types as glucose intolerance increased. Increased CD4 + effector memory tissue-resident cells most strongly associated with altered expression of adipocyte genes critical for lipid metabolism and cellular regulation. Intercellular communication analysis demonstrated enhanced pro-inflammatory and pro-fibrotic signaling between immune cells and stromal cells in PWH with glucose intolerance compared with non-diabetic PWH. Lastly, while cell type-specific gene expression among PWH with diabetes was globally similar to HIV-negative individuals with diabetes, we observed substantially divergent intercellular communication pathways. These findings suggest a central role of tissue-resident immune cells in regulating SAT inflammation among PWH with metabolic disease, and underscore unique mechanisms that may converge to promote metabolic disease.